2010
DOI: 10.1017/s0954579410000520
|View full text |Cite
|
Sign up to set email alerts
|

From child maltreatment to adolescent cannabis abuse and dependence: A developmental cascade model

Abstract: A developmental cascade model tested associations among child maltreatment, internalizing and externalizing psychopathology, social competence, and cannabis abuse and dependence symptoms in a longitudinal cohort (N = 415). Nested structural equation models evaluated continuity and cross-domain influences among broad multi-informant constructs across four developmental periods: age 7 to 9, 10 to 12, 13 to 15, and 15 to 18. Results indicated significant paths from child maltreatment to early externalizing and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
140
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(158 citation statements)
references
References 84 publications
12
140
0
6
Order By: Relevance
“…Furthermore, because they are more likely to suffer more than one type of impairment during early development, victims of child maltreatment are also more susceptible to behavioral problems and psychological disorders both during childhood and the remainder of their development (Kim & Cicchetti, 2010;Rogosch, Oshri, & Cicchetti, 2010). Proctor, Skriner, Roesch and Litrownik (2010) note that little is known about the predictors of behavioral adjustment in individuals exposed to maltreatment.…”
mentioning
confidence: 99%
“…Furthermore, because they are more likely to suffer more than one type of impairment during early development, victims of child maltreatment are also more susceptible to behavioral problems and psychological disorders both during childhood and the remainder of their development (Kim & Cicchetti, 2010;Rogosch, Oshri, & Cicchetti, 2010). Proctor, Skriner, Roesch and Litrownik (2010) note that little is known about the predictors of behavioral adjustment in individuals exposed to maltreatment.…”
mentioning
confidence: 99%
“…23,24 Exposure to maternal depressive symptoms, and the associated 27 This notion of behavioral continuity is supported by research that found that high levels of externalizing behaviors, including aggression, at earlier ages predicts the later engagement in problem behaviors, including substance use. 27,28,30 It is a robust finding that debut age of drug use predicts later substance abuse and future engagement in additional health risk behaviors. 31,32 Additional consequences of early substance use may be reflected in increased suicide risk, 33 which itself represents a significant proportion of young adult and adolescent mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the survey on developmental cascade model that explored a path from child abuse to adolescent cannabis abuse and dependence indicated significant paths from child abuse to early externalizing and internalizing problems and social competence, as well as to cannabis abuse and dependence symptoms in adolescence (Rogosch, Oshri, Cicchetti, 2010).…”
Section: Common Risk and Protective Factorsmentioning
confidence: 99%
“…Speaking in these terms, the development of borderline personality disorder and substance use disorders can be seen as a developmental cascade resulting from adverse early life experience or insecure / preoccupied attachment (Masten & Cicchetti, 2010). For instance, literature on cascade knowledge in the case of developing drug abuse and internalizing disorders, show that these disorders are often linked with early aversive experiences (Rogosch, Oshri & Cicchetti, 2010).…”
Section: Developmental Cascades Modelmentioning
confidence: 99%